Trade‐offs in arthropod conservation between productive and non‐productive agri‐environmental schemes along a landscape complexity gradient. Issue 3 (3rd February 2017) - Mader, Viktoria; Diehl, Eva; Fiedler, Daniela; Thorn, Simon; Wolters, Volkmar; Birkhofer, Klaus
Abstract: Productive and non‐productive agri‐environmental schemes (AES) were developed to support farmland biodiversity. This study compares arthropod predators between productive (organic farming) and non‐productive (sown flowering fields) AES along a landscape complexity gradient. We compared species richness, community composition and community weighted mean body sizes of 12 306 carabids and 4868 spiders in organically managed cereal fields and flowering fields along a landscape complexity gradient. These data were used to evaluate the conservation success of different AES types for a number of exclusive species, financial incentives and benefits for farmers. Carabids only responded to the AES type and their communities had higher species richness in flowering fields. Spider species richness increased with landscape complexity. Community composition differed between AES types for all predator groups, with the composition of ground‐dwelling spiders being additionally affected by landscape complexity. The mean body size of web‐building spiders decreased with landscape complexity and the mean body size of female spiders was larger in flowering fields. Both AES types can contribute to the conservation of predator communities. Species richness increased with non‐productive AES. Agrobiont species occurred more frequently in productive AES. The overall number of exclusive predator species was lower in flowering fields. We emphasise that there is an additive effect of establishing productive and non‐productive AES within the landscape, and a diverse mosaic of different AES types holds the greatest potential to provide a large regional species pool of arthropod predators, while simultaneously guaranteeing financial benefits for farmers from production and subsidies.